2003
DOI: 10.1152/ajpregu.00632.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of opioid receptors reduces body fat in obese rats by decreasing food intake and stimulating lipid utilization

Abstract: Agonists to opioid receptors induce a positive energy balance, whereas antagonists at these receptors reduce food intake and body weight in rodent models of obesity. An analog of 3,4-dimethyl-4-(3-hydroxyphenyl)piperidine, LY255582, is a potent non-morphinan antagonist for μ-, κ-, and δ-receptors ( K i of 0.4, 2.0, and 5.2 nM, respectively). In the present study, we examined the effects of oral LY255582 treatment on caloric intake, calorie expenditure, and body composition in dietary-induced obese rats. Acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…However, in those trials, these agents were nonselective and were given to already obese people. It should be emphasized that more consistent weight-reducing effects in rats were obtained with administration of opioid-receptor antagonists before or during the dynamic phase of obesity development than in animals with preexisting dietary obesity (6,8,24). Also, individual differences in the etiology of obesity (28) may play a role in the efficacy of an opioid receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in those trials, these agents were nonselective and were given to already obese people. It should be emphasized that more consistent weight-reducing effects in rats were obtained with administration of opioid-receptor antagonists before or during the dynamic phase of obesity development than in animals with preexisting dietary obesity (6,8,24). Also, individual differences in the etiology of obesity (28) may play a role in the efficacy of an opioid receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported that nonselective opioid antagonists induce a decrease in RQ, thereby indicating an opioid modulation of lipid oxidation, in rats fed regular and high-fat diets (7,8). However, RQ decreases with reductions in caloric intake (8), and it has not been possible thus far to separate the feeding and metabolic effects of opioids by pharmacological manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound has been carefully studied for its ability to regulate palatable food consumption and body weight in rats (Mitch et al, 1993;Shaw, 1993;Statnick et al, 2003). LY255582 has subnanomolar potency for rat MOR and is 5-and 13-fold selective over KOR and DOR, respectively; thus, it is considered to be relatively nonselective.…”
Section: Discussionmentioning
confidence: 99%
“…Because the cumulative reduction in food consumption was equivalent to the loss of weight, we conclude that GSK1521498 induced fat mass loss through the suppression of food consumption. It is not possible to compare the magnitude of weight loss efficacy for GSK1521498 with that of LY255582 because the models used were inherently different (Shaw, 1993;Statnick et al, 2003). Obese Zucker rats continue to gain weight and treatment of the DIO Long Evans rats started early in the weight gain curve; thus, LY255582 inhibited the progressive weight gain compared with that in the vehicle group.…”
mentioning
confidence: 99%